Dirhodium(II,II) paddlewheel complexes conjugated to a polypyridyl tris-amine scaffold: synthesis and application as asdjncaslpre-catalysts in the hydroformylation of 1-octene - de Doncker, Stephen (Department of Chemistry, 2020)
The hydroformylation reaction is the addition of CO/H2 (synthesis gas) to olefins using a transition-metal catalyst to produce linear and/or branched aldehydes. This reaction is in alignment with the Green Chemistry philosophy, applying principles such as using renewable feedstocks, atom economy, and catalysis. The use of rhodium-based catalysts for hydroformylation offers greater selectivity and catalytic activity under milder conditions compared to cobalt-based counterparts. Furthermore, the introduction of sterically demanding ligands such as phosphines are often introduced to enhance selectivity and activity of active catalysts. The conjugation of dendritic structures to transition-metal catalysts, to form metallodendrimers, may be useful in introducing functional groups that alter electronic and steric factors as well as increasing the activity through multinuclearity. Dirhodium(II,II) complexes contain two rhodium atoms, a metal-metal bond and an oxidation state of 4+ over the bimetallic core, resulting in each rhodium atom having an oxidation state of 2+. The electronic and steric influences can be altered by variety of ligands, bearing alkyl or aryl substituents. The purpose of this investigation was to synthesize and characterize a series of dirhodium(II,II) complexes, a suitably functionalized poly-pyridyl scaffold and conjugation of the synthesized complexes to the periphery of the scaffold to form low valent metallodendrimers. A series of diphenylformamidine ligands bearing electron-withdrawing (fluoro) and electrondonating (methyl) substituents at the ortho- and para-postions on the phenyl rings were synthesized. Two dirhodium(II,II) complexes bearing acetate bridging ligands with methyl or trifluoromethyl groups and four dirhodium(II,II) complexes, bearing synthesized diphenylformamidinate bridging ligands, were obtained. A trisamine-based pyridyl scaffold was synthesized and conjugated to each dirhodium complex to afford the corresponding lowvalent metallodendrimers. All ligands, complexes and metallodendrimers were characterized by spectroscopic (1H, 13C{1H}, 19F NMR, FT-IR) and analytical (mass spectrometry) techniques where applicable. The paddlewheel structure of the complex and pseudo-planar nature of the formamidine N-CN system was confirmed by Single crystal X-ray diffraction analyses. The activity of the synthesized complexes and metallodendrimers were evaluated as catalyst precursors in the hydroformylation of 1-octene. Model reactions were carried out with dirhodium(II,II) tetraacetate as a precursor varying time, pressure and temperature resulting in optimized conditions for the formation of aldehydes, with negligible effects on the activity observed in the presence of mercury. Acetate bearing complexes showed near quantitative conversion (>99.8%) of 1-octene, excellent activity and chemoselectivity toward aldehydes (>98%) with moderate regioselectivity towards linear products (40-44%). Excellent conversion (97-99%), moderate to good chemoselectivity toward aldehyde products (59-87%) and moderate to good regioselectivity (48-71%) where obtained for diphenylformamidine compounds. Coordination of the trisamine-based scaffold leads to a general decrease (ca. 10%) in the chemoselectivity toward aldehydes and an anticipated general increase in the regioselectivity towards linear aldehyde of between 3-5% under optimized hydroformylation conditions. Chemoselectivity towards aldehydes was favoured by electron-donating groups over electronwithdrawing groups in the diphenylformamidinate complexes, with regioselectivity favouring linear aldehydes observed for analogous complexes containing electron-withdrawing groups.